The micro-level dynamics of declining labour share: Lessons from the Finnish great leap - Tomi Kyyrä; Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2006)
In contrast with the experiences of the UK and the US, the distribution of labour and capital income has changed sharply in favour of capital in most Continental European and Nordic countries during the past two decades. We examine forces behind the evolution of the aggregate labour share by analysing the dynamics of labour shares within and between firms/plants in the Finnish business sector. Using a decomposition method applied in labour economics and productivity analysis, we show that much of the decline in the aggregate labour share stems from the reallocation of resources between firms and plants, while labour shares at the firm/plant level have remained relatively stable.
Keywords: J23; J24; D33; 330; Factor income shares; wage policy; decomposition; productivity; Funktionelle Einkommensverteilung; Lohnquote; Lohnpolitik; Produktivität; Finnland